Pengaruh Faktor Fundamental Mikro Terhadap Harga Saham pada Indeks IDX30 - Fitriana, Aning; Sechan, Cathalina (Awatara Publisher, 2024)
This research aims to examine effetc of micro fundamental factors, consist of Current Ratio, Debt to Equity Ratio, and Net Profit Margin on listed the IDX30. This research approach used in quantitatif study and method of multiple linear regression analysis. Purposive sampling used to identify sample. The number of samples used was 80 registered in the 2018-2021 period.. The results for the current ratio variable had asignificant effect on stock prices, the debt to equity ratio and the net profit margin has no significant effect on stock prices. Researchers suggest ivenstor to be careful analysis and review the company's performance before making decision to investment.